2009
DOI: 10.1063/1.3092909
|View full text |Cite
|
Sign up to set email alerts
|

HCN polymers characterized by SSNMR: Solid state reaction of crystalline tetramer (diaminomaleonitrile)

Abstract: The HCN tetramer, diaminomaleonitrile, crystallizes in sheets with amine and nitrile groups of neighboring molecules in close proximity. This suggests the possibility of relatively facile acid-base addition to form a protopeptide polymer. We find that moderate heating under argon indeed results in an unmistakable reaction, with the abrupt transformation of pale crystallites to shrunken dark particles that become electrically conductive upon doping with iodine. Since nearly a quarter of the mass is lost in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
(28 reference statements)
3
18
0
Order By: Relevance
“…The formation of stable five-or six-membered rings is possible from the decyanation of this linear polyamine. Pathway a-1 is consistent with the recent work of Mamajanov and Herzfeld [14], who have studied the solid-state reaction of crystalline DAMN (Scheme 1). The linear polyamide (Pathway a-2) displayed a high tendency to form cyclic components, because the polymerization reactions in solution favor intramolecular cyclizations.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The formation of stable five-or six-membered rings is possible from the decyanation of this linear polyamine. Pathway a-1 is consistent with the recent work of Mamajanov and Herzfeld [14], who have studied the solid-state reaction of crystalline DAMN (Scheme 1). The linear polyamide (Pathway a-2) displayed a high tendency to form cyclic components, because the polymerization reactions in solution favor intramolecular cyclizations.…”
supporting
confidence: 84%
“…These IR bands were assigned to the following functional groups: 3084 cm À 1 (very broad), primary and secondary amines (OH groups of carboxylic acids, and ¼CH in aromatic and unsaturated hydrocarbons may overlap); 1725 and 1665 cm ), and ÀC¼O in carbonyl, carboxylic, and urea compounds (1735 and 1670 cm À 1 ). As in the FT-IR analysis, the 13 C-CP-MAS-NMR spectra of all of our samples were similar and resembled spectra obtained by Garbow et al [25] for the water-insoluble fraction as well as spectra reported by Mamajanov and Herzfeld [14] [15] for an HCN polymer prepared from gas HC 15 N and Et 3 N. The deconvoluted solid-state 13 C-NMR spectrum of our insoluble black HCN polymers displayed the following resonances: i) resonance at 168 ppm, which may correspond to amide groups (ÀCONH 2 ); ii) resonance at 159 ppm, which may correspond to imine and/or heterocyclic groups (ÀC¼NÀ); iii) a group of resonances at 154, 149, and 139 ppm, which may correspond to C-atoms of heterocyclic compounds containing N; iv) a group of low-intensity resonances between 130 and 100 ppm, which may correspond to alkenes ( = = C¼C = = ) and nitriles (ÀC N); and v) a third group of unresolved resonances between 100 and 60 ppm, which may correspond to C-atoms bound to a heteroatom, such as CÀ(N) of amines (Fig. 2, b).…”
supporting
confidence: 80%
“…This fact is very relevant, so that the last studies about the structure of this polymeric system, performed Mamajanov and Herzfeld and based on solid state NMR, propose a polyaminoimidazole as the main chain for HCN polymers [30]. On the other hand, the pyrolytic formation of some of these products, such as formamide and isocyanic acid, is consistent with the presence of amide groups in these HCN polymers.…”
Section: Tablementioning
confidence: 80%
“…Very recently Mamajanov and Herzfeld [28,29] using solid state 13 C and 15 N NMR spectra have investigated the chemical structure of the PHC prepared by a free radical and a base-catalyzed reaction and also obtained by heating the HCN tetramer. Unfortunately, the spectra reported by these authors are different from the solid state 13 C NMR CP-MAS reported in Fig.…”
Section: Chemical Structure Of the Black Insoluble Polymer Formed By mentioning
confidence: 99%